Statin therapy in kidney disease populations: potential benefits beyond lipid lowering and the need for clinical trials. - Baigent, C; Landray, M; Warren, M (2004)
PURPOSE OF REVIEW: This review outlines the limited information currently available on the effects of statins among patients with chronic kidney disease, and summarizes the ongoing randomized trials designed to address this question. RECENT FINDINGS: The effects of fluvastatin on major coronary events among renal transplant patients, and the effects of pravastatin and simvastatin in small subgroups of coronary patients with minor degrees of renal impairment, appear broadly compatible with those observed in trials conducted in non-renal populations. In addition, recent evidence from trials among patients with vascular disease or diabetes suggests that statin therapy may delay progressive loss of renal function. However, there remains substantial uncertainty regarding the effects of statin therapy among patients with established chronic kidney disease (pre-dialysis or dialysis patients). In particular, there does not appear to be a strongly positive relationship between blood cholesterol and cardiovascular events in such patients. This may be because uraemic cardiomyopathy and arteriosclerosis, which cause the majority of these events in chronic kidney disease patients, do not depend strongly on blood cholesterol. SUMMARY: Statins appear effective for the prevention of vascular events in people with established vascular disease and mild renal impairment, and may delay renal disease progression in such individuals. However, the effects of statins in patients with established chronic kidney disease are unknown, and we await the results of ongoing large-scale randomized trials of statin therapy among such patients.